Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pmed.1002670
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid biomarkers of dairy fat consumption and incidence of type 2 diabetes: A pooled analysis of prospective cohort studies

Abstract: BackgroundWe aimed to investigate prospective associations of circulating or adipose tissue odd-chain fatty acids 15:0 and 17:0 and trans-palmitoleic acid, t16:1n-7, as potential biomarkers of dairy fat intake, with incident type 2 diabetes (T2D).Methods and findingsSixteen prospective cohorts from 12 countries (7 from the United States, 7 from Europe, 1 from Australia, 1 from Taiwan) performed new harmonised individual-level analysis for the prospective associations according to a standardised plan. In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
108
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(138 citation statements)
references
References 52 publications
(92 reference statements)
13
108
0
3
Order By: Relevance
“…of obesity [11][12][13][14]. In recent years, researchers have shown that, as metabolites of gut microbiota, short-chain fatty acids (SCFAs) affect the physiological processes of disease by affecting energy supply and immune regulation [15], especially butyric acid (BA), which can alleviate obesity and insulin resistance in mice fed a high-fat diet (HFD) [16].…”
mentioning
confidence: 99%
“…of obesity [11][12][13][14]. In recent years, researchers have shown that, as metabolites of gut microbiota, short-chain fatty acids (SCFAs) affect the physiological processes of disease by affecting energy supply and immune regulation [15], especially butyric acid (BA), which can alleviate obesity and insulin resistance in mice fed a high-fat diet (HFD) [16].…”
mentioning
confidence: 99%
“…As discussed in the introduction, it is becoming clear that each particular FA may play a different role in human health [6,[16][17][18]. In the case of saturated FAs, odd-chain saturated C15:0 and C17:0 have shown to be associated with a lower risk of type 2 diabetes [18]. The levels of odd-chain FFAs C15:0 and C17:0 were estimated and found to be 0.5 ± 0.2 µg/mL and 0.6 ± 0.1 µg/mL in cow milk, respectively and 0.3 ± 0.0 µg/mL and 0.2 ± 0.0 µg/mL in goat milk, respectively.…”
Section: (A)mentioning
confidence: 99%
“…It has been demonstrated that the high circulating odd-chain saturated fatty acid C17:0 is inversely associated with CVD and stroke mortality and potentially associated with higher risk of non-CVD death [17]. A recent large meta-analysis, which pooled the findings from 16 prospective cohort studies, has shown that higher levels of odd-chain saturated fatty acids C15:0 and C17:0 are associated with a lower risk of type 2 diabetes (T2D) [18].…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study among 2907 American adults aged 65 years or older suggested that long‐term exposure to pentadecanoic, heptadecanoic, and trans‐palmitoleic acids are not associated with increased risks of CVD incidence and mortality. Furthermore, a meta‐analysis of 16 prospective cohorts with a total of 63 682 participants showed that higher levels of pentadecanoic, heptadecanoic, and trans‐palmitoleic acids were associated with a lower risk of T2DM. The mechanisms underlying the inverse association between dairy product consumption and T2DM risk remain to be elucidated.…”
Section: Epidemiological Evidence Of the Association Between Milk Andmentioning
confidence: 99%